Rethinking Sportland: A New Research Agenda for the Sport for Development and Peace Sector. (December 2019) - Giulianotti, Richard; Coalter, Fred; Collison, Holly; Darnell, Simon C.
Sport for Development and Peace (SDP) has grown into a huge global field of sport-related activity and intervention and is a heavily researched subject in the social scientific study of sport. In this article, we advance the case for a new research agenda in SDP, in part to contribute more fully to sustainable development through substantial societal change. We argue that SDP research should engage with wider literatures and theories, notably on political economy and development; take full account of structural changes within the development sphere; and examine new areas of intervention within SDP per se. To develop our analysis, our discussion is organized into six main parts. We begin by introducing the concept of "Sportland" to reimagine SDP as a strongly institutionalized field of development activity with its own stakeholder networks. Second, we outline the key aspects of prior SDP/Sportland research on which we seek to build. Third, we examine key changes in the political economy and geopolitics of development, which serve to point Sportland scholars toward engaging with fresh literatures in these fields. Fourth, we explore the implications of these changes to retheorize development. Fifth, we detail new ways ahead for Sportland with regard to policy, practice, and research, with particular reference to the position of different organizational stakeholders within SDP. Finally, we consider specific areas of future intervention and inquiry within Sportland that require the attention of researchers. Our analysis is underpinned by many research studies and projects in Sportland which we have undertaken separately or collectively over at least the last decade.